Social–ecological resilience of communities in facing the cumulative impacts of sand mining and climate change - Prayuda, Adam Bergas; Wijayanto, Dian (Journal of Critical Ecology, 2026)
Background: This study explores the socio–ecological resilience of communities in the Babon Watershed, Demak Regency, in responding to the cumulative impacts of sand mining and climate change. Methods: Using a qualitative case study approach grounded in a constructivist paradigm, data were collected through interviews, focus group discussions, field observations, and document analysis. Findings: The results show that intensive sand mining and rising sea levels have led to environmental degradation, declining agricultural productivity, and socio-economic vulnerability. Despite these challenges, local communities have developed adaptive strategies, including livelihood diversification, collective cooperation, and the strengthening of local institutions. However, resilience remains largely adaptive and short-term rather than transformative. Weak governance, fragmented policies, and economic dependency on extractive activities continue to limit sustainable transformation. Conclusion: The study proposes a three-pillar collaborative framework integrated governance, sustainable economy, and ecological restoration to enhance long-term socio–ecological resilience. Novelty/Originality of this article: These findings contribute to the broader understanding of community-based resilience and offer policy insights for sustainable watershed management in coastal regions of Indonesia.